Clay Science and Technology - Morari Do Nascimento, Gustavo (IntechOpen, 2021)
This book presents the state-of-the-art results of synthesis, characterization, modification, and technological applications of clays, clay minerals, and materials based on clay minerals, such as polymer-clay nanocomposites and clay hybrids. It also presents some important results obtained in the broad area of clays and clay materials characterization. Moreover, this book provides a comprehensive account of polymer and biopolymer-clay nanocomposites, the use of clay as adsorption materials of industrial pollutants, the ceramic industry, and the physical-chemical aspects of aqueous dispersions of clay and clay minerals. This book is beneficial for students, teachers, and researchers who are interested in expanding their knowledge about the use of clays in a diverse range of fields, including nanotechnology, biotechnology, environmental science, industrial remediation, pharmaceuticals, and so on.